The Well-Being of Future Generations Act (Wales, 2015): towards an ecosystem perspective - Beth Cummings (Journal of Entrepreneurship and Public Policy, 2024)
Purpose: Recent times have seen an increasing emphasis on sustainable development as a means of enacting positive regional change. There has also been an emergence in discussions around well-being and its role in promoting holistic sustainable development, such as in Wales through the Well-Being of Future Generations Act (Wales). This paper aims to investigate the role that the Well-Being of Future Generations Act (Wales) currently plays in the ecosystem across South West Wales and ways in which the Well-Being Act could be developed and implemented further. Design/methodology/approach: This qualitative research is based on seven semi-structured interviews conducted with participants drawn from a range of entrepreneurial ecosystem actors in South West Wales, UK. Interview data were analysed using thematic analysis, leading to the establishment of seven themes. Findings: The findings suggest that there is passion and positivity around the Well-Being of Future Generations Act amongst ecosystem actors. However, policymakers need to consider how to extend the reach of the principles of the Well-Being of Future Generations Act beyond public bodies. This could be achieved through more effective communication of the values of the act and increased collaboration between various stakeholders. Originality/value: The concept of well-being remains relatively new in the context of regional economic development and therefore requires closer investigation, particularly how this can be evaluated. Wales is one of three countries worldwide to implement well-being legislation, and there is a lack of research examining the implementation of the Well-Being Act, particularly from regional development and an entrepreneurial ecosystem perspective.